Basal endothelial glycocalyx’s response to shear stress: a review of structure, function, and clinical implications - Vittum, Zoe; Cocchiaro, Samantha; Mensah, Solomon A. (Frontiers in Cell and Developmental Biology, 2024)
The endothelial glycocalyx encompasses the entire endothelial cell, transducing extracellular signals and regulating vascular permeability and barrier functions. The apical glycocalyx, which forms the lumen of the vessel, and the basal glycocalyx, at the smooth muscle cell interface, are often investigated separately as they are exposed to vastly different stimuli. The apical glycocalyx directly senses fluid shear forces transmitting them intracellularly through connection to the cytoskeleton of the endothelial cell. The basal glycocalyx has demonstrated sensitivity to shear due to blood flow transmitted through the cytoskeleton, promoting alternate signaling processes. In this review, we discuss current literature on the basal glycocalyx’s response to shear stress in the context of mechanotransduction and remodeling. The possible implications of basal glycocalyx degradation in pathologies are also explored. Finally, this review seeks to highlight how addressing the gaps discussed would improve our wholistic understanding of the endothelial glycocalyx and its role in maintaining vascular homeostasis.